Obscenity, Child Pornography, and Indecency : Recent Developments and Pending Issues. (U.S. Congressional Research., 2002)
Briefly summarizes recent developments and pending issues in the areas of obscenity, child pornography, and indecency; and highlights P.L. 105-277, the Child Online Protection Act of 1998, and P.L. 106-554, the Children's Internet Protection Act of 2000.